Socio-cultural adjustment and performance of Bangladeshi workers in Malaysia - Uddin, Md Sayed; Md. Noon, Hazizan (IIUM Press, International Islamic University Malaysia, 2017)
The present work is an empirical study of Bangladeshi workers’ socio-cultural adjustment to Malaysian environment. It also investigates the causes of labour migration to Malaysia, workers’ living and working conditions, their level of performance as well as their involvement is social and deviational adjustments. The main thrust of the present study is to explore and assess the three dimensional adjustment of Bangladeshi workers to Malaysian social, work and non-work environment. It has taken three dimensions of adjustment namely general or non-work adjustment, work adjustment and interaction adjustment into consideration, collected relevant information about them and demonstrated workers’ level of adjustment. The study is based on the interview of 100 Bangladeshis migrant workers who were selected according to two stage sampling procedure. On one stage, an area where Bangladeshi workers reside was selected through random sampling procedure. On the second stage, 100 respondents were selected from the area according to convenience sampling procedure. The data were analysed by SPSS version 18.0 software. Cronbach Alpha was computed to ascertain the reliability and validity of the instrument. Multiple regression analysis was used to test the hypotheses. The study revealed that Bangladeshi workers’ adjustment on non-work or general adjustment is quite high but their adjustment is less on work adjustment dimension. It is observed that two factors: motivation to high income and social network, play an important role in Bangladeshi workers’ migration to Malaysia. The other important results was that workers’ degree of comfort (adjustment) with non-work condition was related to their performance of work but their degree of comfort (adjustment) with work adjustment is not related to their work performance. Finally, the study suggested that adequate measures should be taken to provide pre-departure training on job and host county’s culture to the expected migrant workers. The government of the native country should also monitor the activities of recruiting agencies.